Long-term skeletal and dental effects and treatment timing for functional appliances in Class II malocclusion - Franchi, Lorenzo; Pavoni, Chiara; Faltin, Kurt [UNESP]; McNamara, James A.; Cozza, Paola (E H Angle Education Research Foundation, Inc, 2013)
Objective: To analyze the long-term skeletal and dentoalveolar effects and to evaluate treatment timing of Class II treatment with functional appliances followed by fixed appliances.Materials and Methods: A group of 40 patients (22 females and 18 males) with Class II malocclusion consecutively treated either with a Bionator or an Activator followed by fixed appliances was compared with a control group of 20 subjects (9 females and 11 males) with untreated Class II malocclusion. Lateral cephalograms were available at the start of treatment (mean age 10 years), end of treatment with functional appliances (mean age 12 years), and long-term observation (mean age 18.6 years). The treated sample also was divided into two groups according to skeletal maturity. The early-treatment group was composed of 20 subjects (12 females and 8 males) treated before puberty, while the late-treatment group included 20 subjects (10 females and 10 males) treated at puberty. Statistical comparisons were performed with analysis of variance followed by Tukey's post hoc tests.Results: Significant long-term mandibular changes (Co-Gn) in the treated group (3.6 mm over the controls) were associated with improvements in the skeletal sagittal intermaxillary relationship, overjet, and molar relationship (similar to 3.0-3.5 mm). Treatment during the pubertal peak was able to produce significantly greater increases in total mandibular length (4.3 mm) and mandibular ramus height (3.1 mm) associated with a significant advancement of the bony chin (3.9 mm) when compared with treatment before puberty.Conclusion: Treatment of Class II malocclusion with functional appliances appears to be more effective at puberty. (Angle Orthod. 2013;83:334-340.)
Keywords: Functional jaw orthopedics; Class II malocclusion; Cervical vertebral maturation; Cephalometrics; Puberty